2003
DOI: 10.1007/s00424-003-1084-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrolysis-resistant FGF23-R179Q on dietary phosphate regulation of the renal type-II Na/Pi transporter

Abstract: Fibroblast growth factor 23 (FGF23), a phosphaturic factor, is involved in the regulation of renal inorganic phosphate (Pi) reabsorption. Proteolysis-resistant FGF23 mutants expressed in rodents reduce Pi uptake in both intestine and kidney, independent of parathyroid hormone action. In the present study, we investigated whether FGF23 affects dietary regulation of Na(+)-dependent Pi (Na/Pi) cotransport in the rat kidney using wild-type FGF23 and an R179Q mutant, which disrupts a consensus proteolytic cleavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(125 citation statements)
references
References 24 publications
(73 reference statements)
5
119
0
1
Order By: Relevance
“…We previously showed that mutant FGF23 inhibited Na/Pi cotransport activity, the expression of NaPi2a and NaPi2c mRNA and protein in renal brush border membrane vesicles (17,20). In the present study, the hypophosphatemia observed in the mutant FGF23-treated uremic rats might be mainly due to the inhibition of the renal Na/Pi cotransporter.…”
Section: Discussionsupporting
confidence: 48%
“…We previously showed that mutant FGF23 inhibited Na/Pi cotransport activity, the expression of NaPi2a and NaPi2c mRNA and protein in renal brush border membrane vesicles (17,20). In the present study, the hypophosphatemia observed in the mutant FGF23-treated uremic rats might be mainly due to the inhibition of the renal Na/Pi cotransporter.…”
Section: Discussionsupporting
confidence: 48%
“…In addition, fibroblast growth factor 23, a novel phosphaturic factor, acts to decrease type IIc transporter protein and mRNA levels in vivo (8,25). However, other hormonal regulatory mechanisms of the type IIc Na-P i cotransporter remain unknown.…”
Section: Additional Biochemical Findings In Npt2amentioning
confidence: 99%
“…PTH inhibits the expression of the type IIa transporter through the activation of several signal transduction pathways (1,24,25,34). With respect to the distribution of PTH receptor in the renal proximal tubules, hormone binding has been reported in basolateral and in apical membrane preparations (10,18).…”
Section: Additional Biochemical Findings In Npt2amentioning
confidence: 99%
“…El FGF suprime la expresión del cotransportador de sodio y fosfato NPT2a y NPT2c incrementando así la excreción urinaria de fosfato a nivel de túbulo contorneado proximal (18,19) .…”
Section: Factor De Crecimiento De Fibroblastos 23 (Fgf-23)unclassified